2018
DOI: 10.1038/s41585-018-0005-1
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling disparate roles of NOTCH in bladder cancer

Abstract: The Notch pathway has been implicated in both oncogenic and tumour-suppressive roles in cancer depending on the tissue type and cellular context. However, until recently, little was known about the pathway in bladder cancer. Studies have revealed that NOTCH1 copy number and expression are decreased in bladder cancer and NOTCH1 activation in bladder cancer cell lines reduces proliferation, suggesting that NOTCH1 acts as a tumour suppressor. Furthermore, in transgenic models, bladder cancer is promoted by bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 114 publications
0
28
0
3
Order By: Relevance
“…The Notch signaling pathway has both oncogenic and tumor-suppressive effects depending on the organ and cellular context [86]. It involves four receptors (Notch1-4) and five ligands and regulates the transcription of multiple target genes [21].…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The Notch signaling pathway has both oncogenic and tumor-suppressive effects depending on the organ and cellular context [86]. It involves four receptors (Notch1-4) and five ligands and regulates the transcription of multiple target genes [21].…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…It involves four receptors (Notch1-4) and five ligands and regulates the transcription of multiple target genes [21]. The expression of the Notch1 receptor is decreased in BC and its activation decreases cellular proliferation, suggesting that it has a tumor-suppressive role [86]. On the other hand, overexpression of Notch2 promoted cell proliferation, EMT, invasion, and stemness maintenance, and its inhibition decreased malignant phenotypes in vitro and in vivo [87].…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…MFAP5 may activate NOTCH1 signaling by inducing NOTCH1 extracellular domain dissociation 34 . A previous study demonstrated that NOTCH2 is an oncogenic protein in bladder cancer 45 . In order to explore the role of MFAP5 in the NOCTH2 signaling pathway, we knocked down NOTCH2 in T24 and 253J cells and validated knockdown efficiency by western blot (Figure 5A).…”
Section: Resultsmentioning
confidence: 94%
“…In endothelial cells, Notch signaling regulates contact inhibition and cycle arrest (Noseda et al, ). Depending on the cellular context and tissue type, the Notch pathway exerted both tumour‐suppressive and oncogenic action in cancer (Aster, ; Goriki et al, ; Nowell & Radtke, ). MK‐0752 is a potent and specific gamma‐secretase inhibitor that is widely used to prevent Notch receptor activation (Brana et al, ; Chen et al, ; Yuan et al, ).…”
Section: Discussionmentioning
confidence: 99%